STAT3-Inducible Mouse ESCs: A Model to Study the Role of STAT3 in ESC Maintenance and Lineage Differentiation - Yu Qian Wong; Hongyan Xu; Qiang Wu; Xinyu Liu; Chengchen Lufei; Xiu Qin Xu; Xin-Yuan Fu (Stem Cells International)
Studies have demonstrated that STAT3 is essential in maintaining self-renewal of embryonic stem cells (ESCs) and modulates ESC differentiation. However, there is still lack of direct evidence on STAT3 functions in ESCs and embryogenesis because constitutive STAT3 knockout (KO) mouse is embryonic lethal at E6.5–E7.5, prior to potential functional role in early development can be assessed. Therefore, in this study, two inducible STAT3 ESC lines were established, including the STAT3 knockout (InSTAT3 KO) and pSTAT3 overexpressed (InSTAT3 CA) using Tet-on inducible system in which STAT3 expression can be strictly controlled by doxycycline (Dox) stimulation. Through genotyping, deletion of STAT3 alleles was detected in InSTAT3 KO ESCs following 24 hours Dox stimulation. Western blot also showed that pSTAT3 and STAT3 protein levels were significantly reduced in InSTAT3 KO ESCs while dominantly elevated in InSTAT3 CA ECSs upon Dox stimulation. Likewise, it was found that STAT3-null ESCs would affect the differentiation of ESCs into mesoderm and cardiac lineage. Taken together, the findings of this study indicated that InSTAT3 KO and InSTAT3 CA ESCs could provide a new tool to clarify the direct targets of STAT3 and its role in ESC maintenance, which will facilitate the elaboration of the mechanisms whereby STAT3 maintains ESC pluripotency and regulates ESC differentiation during mammalian embryogenesis.